Environmental Concern and Pro-environmental Behaviours in Young and Elderly People - Favara, Jésica Verónica; Moreno, José Eduardo (Revista de Psicología, 2020)
This paper presents some results of a study that is part of a larger research that assesses environmental concerns, pro-environmental behaviours and well-being in young and elder people in Buenos Aires, Argentina. The aim is to compare the results obtained with the environmental concern scale and the pro-environmental behaviour scale in young and elderly people. Significant differences were observed between both groups, which are interpreted in relation to the model of environmental concern proposed by Amérigo, Aragonés, & García (2012) and adapted to the local population (Cassullo, Caballero, Favara, Colombo, & Rusca, 2015) that includes four dimensions: apathy, anthropocentrism, con-nectivity and emotional affinity. Differences were found in relation to the pro-environmental behaviours declared by the participants, observing that apathetic young people are less prone to have pro-environmental behaviours, while those with greater interest would have a greater predilection for these actions. In contrast, in older adults it was ob-served that pro-environmental behaviours are predicted by the emotional connection with nature and the interest in the environment they possess. In older adults, the variables excluded by their low predictive power were anthropocentrism and apathy.